Financial Performance Analysis of the Regional Government of Merangin District in the Fiscal Year 2017-2023 - Sabina Dewanda Putri; Iskandar Sam; Rahayu Rahayu (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the financial performance of the Merangin Regency Government in the 2017-2023 budget year using the financial ratio analysis method. The ratios used include the regional financial independence ratio, the effectiveness and efficiency ratio of Regional Original Income (PAD), the activity ratio (spending harmony), the growth ratio, and the budget solvency ratio. The data used in this study are secondary data obtained from the realization report of the Regional Revenue and Expenditure Budget (APBD) of Merangin Regency during the study period. The results of the analysis show that the financial performance of Merangin Regency fluctuates from year to year. The PAD effectiveness and efficiency ratio shows a fairly good level of effectiveness, although its efficiency still needs to be improved. The regional financial independence ratio is still relatively low, indicating a fairly high dependence on transfer funds from the central government. The activity ratio shows that the allocation of spending is still used more for operational spending than capital spending, which has an impact on the region's ability to build long-term infrastructure. This study provides recommendations for the Merangin Regency Government to improve its strategy in optimizing PAD and managing the budget more efficiently and oriented towards sustainable development..